If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -3) + -3(x + -4) = 1 Reorder the terms: 2(-3 + x) + -3(x + -4) = 1 (-3 * 2 + x * 2) + -3(x + -4) = 1 (-6 + 2x) + -3(x + -4) = 1 Reorder the terms: -6 + 2x + -3(-4 + x) = 1 -6 + 2x + (-4 * -3 + x * -3) = 1 -6 + 2x + (12 + -3x) = 1 Reorder the terms: -6 + 12 + 2x + -3x = 1 Combine like terms: -6 + 12 = 6 6 + 2x + -3x = 1 Combine like terms: 2x + -3x = -1x 6 + -1x = 1 Solving 6 + -1x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 1 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 1 + -6 -1x = 1 + -6 Combine like terms: 1 + -6 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5
| 8+-u=19 | | 4+9b=8b | | 18w+-10+-6=50 | | -45+9x=5x+51 | | x^2+7=-12 | | 2.2x-y=-5 | | 7y+11x=49 | | q-4-2=1 | | -9m+10=-6m-6m-8 | | 2x-174=50-12x | | (3x+5)(9-x)=15(x+3) | | 4w+3s=6 | | 4+5x=-12+x | | 9-4-2=1 | | 4y+-7x=16 | | 3x=112-5x | | (7-4x)=-9 | | 2(4-v)=-(3v-2) | | -6u=-7u+3 | | -35+2x=-x+16 | | 5x-1=13-22 | | 2y+1=3x-2 | | 9=3+3w | | -17=-2p | | x-2(x-1)+3(4-2x)=3x+2(x-5) | | 3=24x-3x | | 3x-122=138-7x | | 4-4v=-3-5v | | 3=27x-3x | | -6(8.5)-2y=41 | | 11y^2+16y-20=0 | | 3(6x-5)-7x=-103 |